Artificial Intelligence Supported Tunnel Lighting System - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
Road tunnel lighting is of paramount importance to ensure eye comfort and safety for drivers. In this study; It is aimed to reduce the illuminance and color temperature changes in the entrances from a bright exterior to a dark tunnel or into a very bright tunnel from a dark environment. In this context, the most accurate illumination for the tunnel was determined by using the fuzzy logic method of artificial intelligence to reduce the changes, and the data of the changes in the external environment taken from the sensors were processed. In-tunnel and out-of-tunnel lighting compatibility is provided with membership functions entered in MatLab program. © 2019 IEEE.
Keywords: color temperature; DiaLux; fuzzy logic; illuminance; tunnel lighting